2018
DOI: 10.1007/s12264-018-0244-4
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Neuromodulatory Therapies for Disorders of Consciousness

Abstract: Treatment for disorders of consciousness (DOCs) is still a Gordian knot. Evidence-based guidelines on the treatment of DOC patients are not currently available, while neuromodulation techniques are seen as a potential treatment. Multiple neuromodulation therapies have been applied. This article reviews the most relevant studies in the literature in order to describe a clear picture of the current state of neuromodulation therapies that could be used to treat DOC patients. Both invasive and noninvasive brain st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 112 publications
0
23
0
2
Order By: Relevance
“…Nowadays non-invasive brain stimulation methods (NIBS), such as transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS), prove themselves as promising tools. Few studies have addressed the application of NIBS, with conflicting results [3]. Thibaut et al in 2014 observed transiently improved signs of consciousness in 13 of 30 MCS patients following severe brain damage as measured by changes in the CRS-R total scores after a single session of tDCS over the left dorsolateral prefrontal cortex (DLPFC), while no effect was seen in VS/UWS subjects [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays non-invasive brain stimulation methods (NIBS), such as transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS), prove themselves as promising tools. Few studies have addressed the application of NIBS, with conflicting results [3]. Thibaut et al in 2014 observed transiently improved signs of consciousness in 13 of 30 MCS patients following severe brain damage as measured by changes in the CRS-R total scores after a single session of tDCS over the left dorsolateral prefrontal cortex (DLPFC), while no effect was seen in VS/UWS subjects [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a non-invasive DBS approach, θ burst TMS pattern, and novel forms of transcranial electrical stimulation, such as HD-tDCS, tACS, and tRNS, have either been described or practiced in this field. [ 49 , 84 86 , 97 , 100 , 102 ] More innovations are worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…La ETD puede inducir neuroplasticidad y modular la función cortical a través de una débil corriente continua en el cuero cabelludo y la EMC es una técnica segura, no invasiva e indolora que también ha demostrado efecto neuromodulador, cuando se administra en forma repetitiva. Ambas pueden actuar como un excitador o un inhibidor de la actividad cerebral en regiones de interés 58 , pero tienen la limitación de estimular superficialmente, perdiendo efecto en núcleos grises profundos. Otras terapias neuromoduladoras, como la estimulación eléctrica del nervio vago y del nervio mediano, igualmente modulan la actividad cerebral funcional 59 .…”
Section: Nuevas Terapias Neuromoduladorasunclassified
“…A pesar de su amplio uso, los defectos en los diseños de estudios, el tamaño de muestral y la falta de un grupo control, han limitado la potencia de las investigaciones. Además, algunos investigadores han señalado preocupación que la potencial sobreestimulación en pacientes no respondedores (específicamente estimulación del nervio mediano) pudiera llevar a una reducción de la percepción de algunos estímulos 58 .…”
Section: Nuevas Terapias Neuromoduladorasunclassified